Web-Based Population Data Information System at Suwaduk Village Office to Improve Service Efficiency - Pegianti, Nanda`; Riadi, Aditya Akbar; Susanto, Arief (Journal La Multiapp, 2025)
The rapid development of information technology has encouraged government agencies, including village offices, to utilize digital systems to improve the effectiveness of data management. At the village level, population data management is still largely done manually or using Microsoft Excel files, which have various limitations in terms of search speed, data security, and information integration. This study aims to design and build a Web-Based Population Data Collection Information System to assist village governments in recording, processing, and presenting population data more effectively and efficiently. This system was developed using the Waterfall method, which consists of the stages of needs analysis, system design, implementation, testing, and maintenance. The implementation results show that this system is able to overcome various previous problems, increasing efficiency, accuracy, and transparency in population data management. Features such as Excel data import with automatic validation, population data and family card management, data conversion history, and automatic generation of certificates, work as expected. Thus, this system has a positive impact on administrative services and data-based decision-making in Suwaduk Village.